EVALUASI TINGKAT PELAYANAN JAMINAN KESEHATAN NASIONAL BPJS DALAM PERSPEKTIF HAM - Lisa Octavia Apliana Dewi (Labor Program Studi Pendidikan Sosiologi, 2022)
The purpose of this study was to determine the National Health Insurance (JKN) facilities throughout Indonesia, and to determine the level of hospital service by comparing patients using BPJS health facilities and general patients. This research method uses literature review / journal data collection from several authors and the results of research between one author and another have the same results in one case. Justice and the right to obtain proper health and welfare in the perspective of human rights are still not felt by the entire population, discriminatory services against BPJS patients, until the treatment rooms for BPJS health care service users are still limited, making poor people have to pay for medical expenses and BPJS health facilities cannot be used. Here there is a need for improvements from the Government in implementing classless hospitals and an increase in the number of specialist doctors, especially so that they are available in Hospitals in Rural Areas. It is hoped that the role of the Government in corrective actions towards Health Services will be in accordance with as stated in the 1945 Constitution (UUD'45) article 28 H paragraph (1) which states that everyone has the right to obtain health services, then in Article 34 paragraph (3 ) stated that the State is responsible for the provision of adequate health service facilities and public service facilities.